PERAN SYAHBANDAR DALAM KESELAMATAN PELAYARAN - Dedeh Suryani; Aprilia Yudi Pratiwi; Sunardji; Andi Hendrawan (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2018)
Safety of shipping is very important and occupies a central position in all aspects of the shipping world. Aspects inherent in the safety of shipping include characteristics of attitudes, values, and activities concerning the importance of the fulfillment of safety and security requirements relating to transport in waters and ports.This paper discusses the role of syahbandar in the cruise shelter. Safety of shipping is an integral part of the role of syahbandar, the study of this article is a literature review or library research. The results show that the role of syahbandar is very important in the safety system of shipping